DETERMINANTS OF MSME EXPORT PERFORMANCE IN THE AFRICAN MARKET: THE ROLE OF ECONOMIC STRENGTH AS A MEDIATOR OF MSME DEVELOPMENT, BILATERAL TRADE, AND GOVERNMENT SUPPORT - Meilina Sukmarini; Hesri Mintawati; Sitti Hikmawatty; M. Luthfi Abdul Ajiz (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the effects of MSME development, bilateral trade opportunities, and government support on MSME export performance in the African market and tests the mediating role of economic strength. The limited contribution of Indonesian MSME exports remains a challenge to improving national competitiveness in the global market. At the same time, the expansion of Indonesia's economic cooperation with African countries creates new opportunities for MSMEs to diversify their export markets. However, internal constraints, including limited business capacity, access to financing, innovation capability, and export readiness, continue to affect many MSME operators. Moreover, the effectiveness of government support and the use of international trade opportunities in promoting MSME export success still require more comprehensive empirical evidence. This study uses a quantitative explanatory survey of 120 upgraded MSMEs in Sukabumi City, West Java, selected through purposive sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) in SmartPLS 4. The results show that bilateral trade opportunities and government support have positive and significant effects on MSME economic strength. By contrast, MSME development does not have a significant effect on economic strength. In the export-performance model, only government support has a positive and significant effect on MSME export performance. MSME development, bilateral trade opportunities, and economic strength do not have significant effects on export performance. The mediation tests also show that economic strength does not mediate the relationships between MSME development, bilateral trade opportunities, or government support and MSME export performance. These findings indicate that MSME export success in non-traditional markets depends not only on stronger internal business capacity but also, and more substantially, on effective institutional support and government policy. Theoretically, the study provides evidence that the institutional perspective has a more dominant role than internal resources in explaining MSME internationalization in emerging markets. Practically, the results can guide governments and other stakeholders in designing more targeted and integrated MSME export-development programs that improve access to international markets.